2011
DOI: 10.1111/j.1439-0396.2011.01255.x
|View full text |Cite
|
Sign up to set email alerts
|

Amending reduced fish‐meal feeds with marine lecithin, but not soy lecithin, improves the growth of juvenile cobia and may attenuate heightened responses to stress challenge

Abstract: Sparing of marine resources in aquafeeds can be environmentally and economically advantageous; however, fish meal (FM) replacement can affect the production performance and physiological competence. Phospholipids are increasingly understood to be involved in maintaining growth and vigour in fish and may be deficient in reduced FM formulations. Accordingly, we evaluated the growth and stress tolerance of juvenile cobia fed typical (50% FM) or reduced FM feeds (12% FM) with or without phospholipid amendment [1% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 45 publications
0
15
1
Order By: Relevance
“…In addition, contrary to the lack of dietary effect on plasma lactate in the study ofTrushenski et al (2013), a higher lactate concentration in plasma of red drum fed the soya-based diets were observed in this study. It is unclear whether species (red drum versus cobia, Rachycentron canadum L.), dietary plant-protein level (644 versus 471.2 g/kg) and/or experimental procedures may help to explain the observed differences in plasma lactate.The characterization of the gut microbiota in this study aided at evaluating the potential effects of dietary SP and GBA in juvenile red drum.…”
contrasting
confidence: 99%
“…In addition, contrary to the lack of dietary effect on plasma lactate in the study ofTrushenski et al (2013), a higher lactate concentration in plasma of red drum fed the soya-based diets were observed in this study. It is unclear whether species (red drum versus cobia, Rachycentron canadum L.), dietary plant-protein level (644 versus 471.2 g/kg) and/or experimental procedures may help to explain the observed differences in plasma lactate.The characterization of the gut microbiota in this study aided at evaluating the potential effects of dietary SP and GBA in juvenile red drum.…”
contrasting
confidence: 99%
“…Alone, these minor differences in protein content and feed intake are unlikely to have substantially affected growth, but perhaps the combination of these effects-not partially hydrogenated soybean oil or PL supplementation-is to blame for the slightly impaired performance observed. Although previous research has suggested that the provision of marine-origin phospholipid is a means of improving the performance and physiological competence of Cobias fed reduced-fish meal feeds, previous and current results suggest that the benefits of soybean lecithin supplementation in juvenile Cobia feeds are limited (Trushenski et al 2013). Niu et al (2008aNiu et al ( , 2008b reported that PL supplementation (8% TABLE 5.…”
Section: Discussionmentioning
confidence: 59%
“…Previous studies on sea bream showed that the replacement of dietary fish oil with vegetable oils (such as linseed oil, but not soybean oil) led to significantly higher plasma cortisol concentrations after acute stress , and significantly higher levels of cortisol release by the head kidney after adrenocorticotropic hormone (ACTH) stimulation (Ganga et al 2011). Similar results have also been shown in sunshine bass (Morone saxatilis) and cobia (Rachycentron canadum) fed reduced fish meal feeds (Laporte and Trushenski 2012;Trushenski et al 2013). The replacement of fish oil with vegetable oils devoid of LC-PUFA results in lower tissue concentrations of arachidonic acid, essential fatty acids and DHA (Ganga et al 2011).…”
Section: Physiological Traitsmentioning
confidence: 60%